Key issues of public relations of Europe: Findings from the European Communication Monitor 2007-2014 - Verčič, Dejan; Verhoeven, Piet; Zerfass, Ansgar (Instituto de Investigación en Relaciones Públicas, 2014)
European Communication Monitor is the largest longitudinal research project in public relations practice in the world. Data collected annually from 2007 to 2014 show that practitioners perceive five issues as the most important for their work: linking business strategy and communication, coping with the digital evolution and social web, building and maintaining trust, dealing with the demand for more transparency and active audiences, and dealing with the speed and volume of information flow. Perception of the importance of various issues for the practice of public relations is largely dependent on the gender, geography (division between Northern and Western vs. Southern and Eastern Europe), and sector in which a practitioner works (corporate, government, NGO or agency). While gender and sectorial differences studied in academic public relations literature, divisions in public relations practice between North-Western and South-Eastern Europe are largely ignored.
Temas clave de las relaciones públicas en Europa: Resultados del European Communication Monitor 2007-2014
Keywords: Gestión de la comunicación; Relaciones públicas; Comunicación en la empresa; Public Relations; Corporate communication; Communication management